Integrating Women's Rights and Climate Migrant Protection: Bridging Gaps in Vietnam - Khanh Linh Ta; Pham Khanh Linh (Human Rights in the Global South)
Southeast Asia faces escalating environmental challenges, making it a hotspot for extreme weather and climate-induced displacement. By 2050, the lower Mekong sub-region is projected to experience 3.3 to 6.3 million internal displacements due to climate change, potentially affecting up to 2.7% of the population. Climate migration is a gendered issue, with women disproportionately vulnerable to genderbased violence, trafficking, and inadequate access to essential services such as sanitation, and sexual, reproductive, and mental health care. Despite growing attention to climate migration, limited research explores the intersectional challenges faced by female climate migrants. This study investigates the identity and experiences of female climate migrants globally and in Vietnam, emphasizing their unique vulnerabilities during and after displacement. Using a comparative analysis of international and Vietnamese legal frameworks, the study highlights gaps in their protections. Accordingly, current laws often address these women either as victims of climate crises or as female migrants but fail to consider the overlap of these identities. Findings reveal the urgent need for a holistic, rights-based approach that acknowledges the intersectional experiences of female climate migrants. Such an approach could enhance their protection and resilience while addressing critical gaps in both international and domestic legal systems. The study contributes to the existing literature by proposing a framework that integrates genderresponsive and climate-specific considerations into migration policies, ensuring comprehensive protection for this marginalised group. This research underscores the importance of tailored legal and policy interventions to safeguard the rights and dignity of female climate migrants, advocating for more inclusive and equitable responses to climate-induced migration.